Analisis Faktor Yang Mempengaruhi Aktivitas Instrumen Derivatif Valuta Asing Sebagai Pengambilan Keputusan Hedging (Studi Kasus Pada Perusahaan Sub Sektor Batubara Yang Terdaftar Di Bei Periode 2017-2021) - Daffa Fadhlurrahman Hartadi; Utami, Kery (Ekonomi dan Bisnis, 2023)
Hedging is an alternative of risk management that aims to protect the assets of company from losses caused by the risk. This study’s purpose is to analyze the influence of independent variables which include Liquidity, Leverage, Firm Size, and Managerial Ownership on hedging decision using derivative instruments at coal companies listed on the Indonesia Stock Exchange in 2017-2021. Sample selection method used in this research is purposive sampling method with the provision of the company that publishes full financial statements in which 16 companies were included in the coal companies as sample. This research used logistic regressions analysis technique, to find sets of variables that affect the probability the use of derivative instruments as hedging activities. The results of this study found that: (1) Leverage and Firm Size variables have a positive and significant effect on hedging decisions using derivatives instruments and (2) Liquidity and Managerial Ownership have a negative and insignificant effect on hedging decisions using derivatives instruments.   Keywords: Liquidity, Leverage, Firm Size, Managerial Ownership, and Hedging